(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The combat with short-edged weapons has a long tradition in Iran. There are several traditional types of Persian knives and daggers. They can generally be classified into three main categories that were used by Persian warriors in close cambat: kard (knife), xanjar (dagger), and pisqabz (a type of knife/dagger with an S-shaped blade). The pisqabz was also called desne. The following article presents these different weapons, analyzing their basic features and variations, the way of carrying and unsheathing them, and the corresponding techniques of use of each weapon.